Neurologic Complications in Adult Post-cardiotomy Cardiogenic Shock Patients Receiving Venoarterial Extracorporeal Membrane Oxygenation: A Cohort Study - Hou, Dengbang; Wang, Hong; Yang, Feng; Hou, Xiaotong (Frontiers in Medicine, 2021)
Background: This study aims to describe the prevalence of neurologic complications and hospital outcome in adult post-cardiotomy cardiogenic shock (PCS) patients receiving veno-arterial extracorporeal membrane oxygenation (V-A ECMO) support and factors associated with such adverse events. Methods: 415 adult patients underwent cardiac surgery and received V-A ECMO for more than 24h because of PCS. Patients were divided into two groups: those who developed a neurological complication and those who did not (the control group). Multivariable logistic regression was performed to identify factors independently associated with neurologic complications. Results: Neurologic complications occurred in 87 patients (21.0%), including cerebral infarction in 33 patients (8.0%), brain death in 30 patients (7.2%), seizures in 14 patients (3.4%), and intracranial hemorrhage in 11 (2.7%) patients. In-hospital mortality in patients with neurologic complications was 90.8%, compared to 52.1% in control patients (p <0.001). In a multivariable model, the lowest systolic blood pressure (SBP) level pre-ECMO (OR, 0.89; 95% CI: 0.86-0.93) and aortic surgery combined with coronary artery bypass grafting (OR, 9.22; 95% CI: 2.10–40.55) were associated with overall neurologic complications. Age (OR, 1.06; 95% CI: 1.01-1.12) and lowest SBP (OR, 0.81; 95% CI: 0.76-0.87) were correlative factors of brain death. Coagulation disorders (OR, 9.75; 95% CI: 1.83–51.89) and atrial fibrillation (OR, 12.19; 95% CI: 1.22–121.61) were shown to be associated independently with intracranial hemorrhage, whereas atrial fibrillation (OR, 8.15; 95% CI: 1.31–50.62) was also associated with cerebral infarction. Conclusions: Neurologic complications in adult PCS patients undergoing VA ECMO support are frequent and associated with higher in-hospital mortality. Identified risk factors of neurologic complications might help to improve ECMO management and might reduce their occurrence.